2020
DOI: 10.3390/ijerph18010263
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Educational Interventions on Breast Cancer Screening Uptake, Knowledge, and Beliefs among Women: A Systematic Review

Abstract: There have been various systematic reviews on the significance of educational interventions as necessary components to encourage breast cancer screening (BCS) and reduce the burden of breast cancer (BC). However, only a few studies have attempted to examine these educational interventions comprehensively. This review paper aimed to systematically evaluate the effectiveness of various educational interventions in improving BCS uptake, knowledge, and beliefs among women in different parts of the world. Following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 59 publications
0
26
0
Order By: Relevance
“…Educational programs play a significant role in improvement of women knowledge, beliefs and practice in regard to breast cancer screening [ 14 ]. Trainings based on the scientific models and theories, according to their conceptual framework, provide a purposeful instrument for empowerment of the target population for promotion of individuals' control on their own health [ 14 , 15 ]. The Health Belief Model (HBM) is one of the most popular models used for prevention of diseases and identification of the effective factors in screening behaviors [ 14 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Educational programs play a significant role in improvement of women knowledge, beliefs and practice in regard to breast cancer screening [ 14 ]. Trainings based on the scientific models and theories, according to their conceptual framework, provide a purposeful instrument for empowerment of the target population for promotion of individuals' control on their own health [ 14 , 15 ]. The Health Belief Model (HBM) is one of the most popular models used for prevention of diseases and identification of the effective factors in screening behaviors [ 14 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Trainings based on the scientific models and theories, according to their conceptual framework, provide a purposeful instrument for empowerment of the target population for promotion of individuals' control on their own health [ 14 , 15 ]. The Health Belief Model (HBM) is one of the most popular models used for prevention of diseases and identification of the effective factors in screening behaviors [ 14 , 16 ]. The model assumes that preventive behaviors are based on individuals' beliefs.…”
Section: Introductionmentioning
confidence: 99%
“…This model is one of the most widely used social cognition models to predict health behaviors and is founded on six fundamental constructs: perceived susceptibility, perceived severity, perceived benefits, perceived barriers, cues to action, and self-efficacy [ 23 ]. Previous research has suggested that HBM-based educational interventions could help to improve knowledge and beliefs about breast cancer and, subsequently, to promote screening uptake among women [ 22 , 24 ]. However, this model has limitations in that it places narrowly defined determinants of behavior in a specific relationship to one another, completely isolated from social context [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, providing programs that promote health literacy, focused on BC and the significance of screening methods, including BSE, could reduce concerns and motivate them to practice BSE in a systematic basis. 28 30 The promotion of alternative, technology enhanced tools could facilitate the empowerment of women in such basis. 33 , 54 …”
Section: Discussionmentioning
confidence: 99%
“…Data from various research areas conclude that health literacy aiming interventions can shift perceptions of women toward BC screening. 28 31 Technology derived interventions are feasible and provide a cost-effective method of early BC screening. 32 , 33 …”
Section: Introductionmentioning
confidence: 99%